简便计算:(1+1/11+1/13+1/17)*(1/11+1/13+1/17+1/19)-(1+1/11+1/13+1/17+1/19)*(1/11+1/13+1/17)

来源:学生作业帮助网 编辑:作业帮 时间:2022/10/04 20:16:07
简便计算:(1+1/11+1/13+1/17)*(1/11+1/13+1/17+1/19)-(1+1/11+1/13+1/17+1/19)*(1/11+1/13+1/17)

简便计算:(1+1/11+1/13+1/17)*(1/11+1/13+1/17+1/19)-(1+1/11+1/13+1/17+1/19)*(1/11+1/13+1/17)
简便计算:(1+1/11+1/13+1/17)*(1/11+1/13+1/17+1/19)-(1+1/11+1/13+1/17+1/19)*(1/11+1/13+1/17)

简便计算:(1+1/11+1/13+1/17)*(1/11+1/13+1/17+1/19)-(1+1/11+1/13+1/17+1/19)*(1/11+1/13+1/17)

1/11+1/13+1/17=A
1/11+1/13+1/17+1/19=B
原式=(1+A)×B-(1+B)*A
=B+A×B-A-A×B
=B-A
=1/19